Independent Commissioners, Inventory Intensity, Capital Intensity and Aggressiveness Tax - Safitri, Cindy Eka; Oktaviany, Firda Sari; Samosir, Refina Tasari; Nurjaman, Ulung; Suripto, Suripto (Universitas Pamulang, 2024)
Study this aims to test the influence of commissioner independence, inventory intensity, and capital intensity against aggressiveness tax. Variables used in the study are commissioner independence, inventory intensity, and capital intensity. At the same time, the variable dependent on research is aggressiveness measured taxes using ETR. A study was carried out on 53 consumer goods industry sector companies on the Indonesian Stock Exchange, using purposive sampling through criteria that have been determined. Data from 16 companies were created as sample studies with observation for the five years 2014 - 2018, so the total observations used are as many as 80 samples. The data used is secondary data reported from the finance annual company consumer goods industry sector for 2014 - 2018. Research uses analysis of multiple linear regression for testing the hypothesis. Research shows that commissioner independence and inventory intensity do not influence aggressiveness tax. In contrast, capital intensity affects positive and significant aggressiveness tax and further commissioner independence, inventory intensity, and capital intensity together with the same influential aggressiveness tax.